Stay close to urban green spaces: current evidence on cultural ecosystem services provision - Vidal, Diogo Guedes (2021)
Research suggests that access to urban green spaces (UGS) is crucial to support public and environmental health through ecosystem services (ES) provision. However, Cultural ecosystem services (CES), due to their connections to human emotion, a deep meaning, fulfilment, and motivation, have been less studied. CES provision in UGS are central to well-being, contributing to improving mental and physical health outcomes, as well as enhancing social cohesion. Accordingly, this systematic review aims to contribute to a better understanding of CES provision by UGS.